2023
DOI: 10.1113/jp284204
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dorsal premotor cortex differentially influences I‐wave excitability in primary motor cortex of young and older adults

Abstract: Previous research using transcranial magnetic stimulation (TMS) has demonstrated weakened connectivity between dorsal premotor cortex (PMd) and motor cortex (M1) with age. While this alteration is probably mediated by changes in the communication between the two regions, the effect of age on the influence of PMd on specific indirect (I) wave circuits within M1 remains unclear. The present study therefore investigated the influence of PMd on early and late I‐wave excitability in M1 of young and older adults. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous work from our group (Liao et al, 2023) and others (Meng et al, 2020) have reported that the application of iTBS to PMd broadly increases M1 excitability in young adults. This effect is thought to stem from the induction of LTP-like effects within PMd (Meng et al, 2020), resulting in increased excitability within M1 when assessed with PA and AP single-pulse TMS (PA 1mV , AP 1mV , PA 0.5mV , AP 0.5mV ) (Liao et al, 2023).…”
Section: Pmd Itbs and M1 Excitabilitymentioning
confidence: 67%
See 3 more Smart Citations
“…Previous work from our group (Liao et al, 2023) and others (Meng et al, 2020) have reported that the application of iTBS to PMd broadly increases M1 excitability in young adults. This effect is thought to stem from the induction of LTP-like effects within PMd (Meng et al, 2020), resulting in increased excitability within M1 when assessed with PA and AP single-pulse TMS (PA 1mV , AP 1mV , PA 0.5mV , AP 0.5mV ) (Liao et al, 2023).…”
Section: Pmd Itbs and M1 Excitabilitymentioning
confidence: 67%
“…Sample size for the present study was determined using simulation-based power estimations on Rstudio (version 2023.12.1 + 402) (Team, 2015) using 'lme4' (Bates et al, 2015) and 'simr' (Green & MacLeod, 2016) packages. Our previous work assessing the effects of PMd iTBS on M1 excitability in young and older adults (Liao et al, 2023) revealed a fixed effects coefficient of À0.349 for the intervention that was used as an unstandardised measure of effect size (Green & MacLeod, 2016). This value was lowered by 15% (À0.297) to account for biases in power calculations derived from experimental data (Green & MacLeod, 2016) and revealed a required sample size of 25 total participants to observe a small to moderate effect of PMd iTBS on M1 excitability, given α = 0.05 and 1 -β = 0.9.…”
Section: Sample Size and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…When stimulating M1 with TMS, distinct descending volleys can be measured in the corticospinal neurons and will summate at the level of the spinal cord to finally elicit an MEP in the muscle corresponding to the stimulated M1 area. When stimulating at higher intensities, this results in direct activation of the corticospinal neurons (i.e., D-wave), whereas lower intensities rather elicit an indirect activation of M1 via mono- and polysynaptic inputs of the local intracortical network (I-waves), to which PMd contributes (Di Lazzaro et al, 2001, Groppa et al, 2012, Liao et al, 2023, Rossini et al, 2015, Ziemann et al, 1996). Based on the emerging I-waves, choices in the dsTMS stimulation protocol such as the intensity of the CS and TS applied to PMd and M1 respectively, their timing (ISI), and the coil orientation (Di Lazzaro et al, 2001) can influence the pattern of activation in M1 and the subsequent muscle response.…”
Section: Discussionmentioning
confidence: 99%